Peculiarities of the growth and the content of endogenous cytokinins in the mycelial biomass of basidial mushrooms Hericium coralloides and Fomitopsis officinalis growing in vitro - Vedenicheva, N.P.; Al-Maali, G.A.; Bisko, N.A.; Shcherbatiuk, M.M.; Kosakivska, I.V. (Reports of the National Academy of Sciences of Ukraine, 2018)
Growth dynamics and features of the accumulation of endogenous cytokinins in the mycelial biomass of medicinal basidial mushrooms Hericium coralloides and Fomitopsis officinalis at the various stages of cultivation in vitro have been analyzed. Accumulation dynamics of individual cytokinin forms is found to be species-specific. The maximum cytokinin content in H. coralloides occurred in the phase of an intensive growth, and the growth slowed down along with a gradual decrease in their levels. In F. officinalis, no clear correlation between the mycelial biomass growth and the accumulation of cytokinins was observed. Changes in the endogenous cytokinins accumulation pattern detected during the mycelial biomass growth are considered as an indirect evidence of the involvement of these phytohormones in the regulation of the growth and development of basidial mushrooms.